Analysis Of The Role Of The Lad Office In The Use Of The Partner Aapplication (Study of Electronic Registration of Village Government Land Assets in Jepara Regency) - Wahyu Bachrudin Bachrudin (Faculty of Law, Universitas Negeri Semarang, 2025)
The Mitra Application is a platform that integrates the National Land Agency with partners. However, the fact is that there are 16 Mitra Kerja Application from 184 Village Governments in Jepara Regency. Which shows that the use of the Mitra Kerja application is still relatively low. This study aims to analyze the role of the Jepara Regency Land Office in increasing the use of the Mitra Karya Application in electronic registration of Government land assets in Jepara Regency, including factors that influence the low number of users of the mirakerja application. The research method used is Qualitative, with an empirical legal approach and qualitative descriptive data techniques. The data sources for this study are primary and secondary data. Primary data is obtained directly from literature studies, observations and interviews. The location of the research is at the Jepara Regency Land Office (ATR / BPN). The results of the study show that the low use of the Mitra Kerja application is caused by the readiness of the infrastructure in the system which often experiences downtime and unstable signals and limited human resources for Mitra Kerja application holders. With these infrastructure constraints, the development of partner applications is slower, and the lack of human resources is an obstacle in providing services that take longer. As an effort to increase the use of partner applications, it is necessary to provide training to employees, especially holders of partner applications and add employees according to needs, implement monitoring and also carry out maintenance and system updates on a scheduled basis to ensure that the software and servers continue to run optimally. With this research, it is expected to provide a contribution to developing partner applications more effectively and can be utilized optimally, so that the integration of the National Land Agency with partners runs optimally.